Metastatic Brain Tumor in the Cerebellopontine Angle from Gastric Cancer: A Case Report - Uchimura, Masahiro; Kambara, Mizuki; Hayashi, Kentaro; Takigawa, Haruo; Anno, Yuichi; Akiyama, Yasuhiko (Asian Journal of Neurosurgery, 2022)
Cerebellopontine angle (CPA) tumors are a common type of benign tumors, which are similar to vestibular schwannomas; however, the incidence of CPA metastasis is rare. Moreover, brain metastasis from gastric tumors is a rare occurrence, with an incidence of less than 1% in clinical cases. In this study, we report the case of a 71-year-old man who was admitted to our hospital with symptoms of nausea and gait instability for the past 1 week. He had no remarkable medical history. Magnetic resonance imaging revealed a tumor in the left CPA. Intraoperative diagnosis indicated the presence of metastatic papillary carcinoma. Postoperatively, gastric endoscopy revealed a protruding mass on the cardia of the stomach, which was histopathologically similar to that of the resected brain tumor. The patient underwent adjuvant cyberknife radiotherapy and chemotherapy. A prompt biopsy of the brain tumor is essential if any findings suggest malignancy.
Keywords: cerebellopontine angle; metastasis; gastric cancer; carcinomatous meningitis